TELEDENTISTRY: STRATEGI MARKETING PELAYANAN KESEHATAN GIGI DAN MULUT DI ERA PANDEMI COVID-19: SYSTEMATIC REVIEW - Sari, Noormaya; Sulistiadi, Wahyu (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2022)
During COVID-19 pandemic, most patients were unwilling to visit the hospital because of fear of COVID-19 contracted, including dental patients, then led to a decrease in the number of patients visits to dental clinics. Hospital managements should have the right marketing strategy so that this situation does not interfere with the operation and income of the hospital. One of the dental service concept that can be developed during the COVID-19 pandemic is teledentistry. The design of this study is a systematic review that searches correlation between dental patients and COVID-19 and marketing strategy. As a result, several studies said that teledentistry could be well applied during the COVID-19 pandemic and had various benefits such as more efficient services, wider service affordability and increase access to service from dentist to the patient. So that in terms of marketing strategy, teledentistry is a service innovation in the field of dental dan oral health that can be applied well during the COVID-19 pandemic. Government's regulation related to teledentistry are needed so that hospitals can be better implement this service concept in the future.